2000
DOI: 10.1016/s0029-7844(99)00607-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of lymph node palpation to determine need for lymphadenectomy in gynecologic malignancies

Abstract: Obstetrics & Gynecology 95 (2000) 553-556. doi:10.1016/S0029-7844(99)00607-9Received by publisher: 1999-06-25Harvest Date: 2016-01-04 12:20:32DOI: 10.1016/S0029-7844(99)00607-9Page Range: 553-55

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…These authors suggested that systematic lymphadenectomy should be performed, rather than lymph node sampling, to determine the therapeutic impact of lymph node resection in epithelial ovarian cancers. Determining nodal metastases by palpation at the time of surgery has been found to have significant limitations (Petru et al, 1994;Arango et al, 2000;Eisenkop and Spirtos, 2001;Tangjitgamol et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that systematic lymphadenectomy should be performed, rather than lymph node sampling, to determine the therapeutic impact of lymph node resection in epithelial ovarian cancers. Determining nodal metastases by palpation at the time of surgery has been found to have significant limitations (Petru et al, 1994;Arango et al, 2000;Eisenkop and Spirtos, 2001;Tangjitgamol et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported a false-negative rate of 36% for intraoperative palpation in 126 women with gynecologic cancers undergoing LND, with a palpation sensitivity and specificity of 72 and 81%, respectively (Arango et al, 2000). Even with experienced hands, 36% of pelvic lymph nodes could not be determined using palpation.…”
Section: 6353 Risk Factors For Lymph Node Metastases With Endometriamentioning
confidence: 99%
“…They were therefore placed in a separate schema from carcinomas in the AJCC 7th edition. 11,27 Carcinosarcoma (formerly known as malignant mixed M€ ullerian tumors) continue to be staged as carcinomas. Adenosarcoma of the uterus is a rare mixed neoplasm that includes both a benign epithelial component and a malignant stromal element.…”
Section: Analytic Cohortsmentioning
confidence: 99%